Bilateral sensory deprivation of trigeminal afferent fibres on corticomotor control of human tongue musculature: a preliminary study. (5th June 2016) - Kothari, M.; Baad‐Hansen, L.; Svensson, P.
Summary: Transcranial magnetic stimulation (TMS) has demonstrated changes in motor evoked potentials (MEPs) in human limb muscles following modulation of sensory afferent inputs. The aim of this study was to determine whether bilateral local anaesthesia (LA) of the lingual nerve affects the excitability of the tongue motor cortex (MI) as measured by TMS. The effect on MEPs after bilateral LA of the lingual nerve was studied, while the first dorsal interosseous (FDI) muscle served as a control in ten healthy participants. MEPs were measured on the right side of the tongue dorsum in four different conditions: (i) immediately prior to anaesthesia (baseline), (ii) during bilateral LA block of the lingual nerve, (iii) after anaesthesia had subjectively subsided (recovery) and (iv) 3 h after bilateral lingual block injection. MEPs were assessed using stimulus–response curves in steps of 10% of motor threshold (T). Eight stimuli were given at each stimulus level. The amplitudes of the tongue MEPs were significantly influenced by the stimulus intensity ( P < 0·001) but not by condition ( P = 0·186). However, post hoc tests showed that MEPS were statistically significantly higher during bilateral LA block condition compared with baseline at T + 40%, T + 50% and T + 60% ( P < 0·028) and also compared with recovery at T + 60% ( P = 0·010) as well as at 3 h after injection at T + 50% and T + 60% ( P < 0·029). Bilateral LA block of the lingual nerve seems to be associated with a facilitation of the corticomotor pathways related to the tongue musculature.